Intermodal Competition in The London-Paris Passenger Market: High-Speed Rail and Air Transport - Christiaan Behrens; Eric Pels (Tinbergen Institute, 2009)
This paper studies inter- and intramodal competition in the London-Paris passenger market. Using revealed preference data, we estimate nested and mixed multinomial logit models to examine passenger behaviour in the London-Paris market. We present a case study on the relocation of Eurostar services from Waterloo International to St Pancras International station. The results show that competition is present in this market. Demand is elastic, and passengers are heterogeneous in their valuation of fares and accessibility. Aviation and high-speed rail are homogenous in unobserved effects. The large market share of the Eurostar and the withdrawal of aviation alternatives indicate that competition will decline in the long-run.
Keywords: R40; R41; 330; inter- and intramodal competition; nested logit; mixed logit; aviation; rail; Verkehrsträgerwettbewerb; Hochgeschwindigkeitsverkehr; Luftverkehr; London; Paris